Lasting Screen Stars Images that Fade and Personas that Endure - Bolton, Lucy.; Wright, Julie Lobalzo; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Lasting Stars examines the issue of stardom and longevity and investigates the many reasons for the persistence or disappearance of different star personas. Through a selection of chapters that look at issues such as inappropriate ageing, national identity and physical characteristics, this book will be the first volume to consider in depth and breadth the factors that affect the longevity of film stardom. The range of stars includes popular stars who are approached from fresh angles (Brando, Loren), less popular stars whose lower-profiles than their peers may be surprising (Taylor, Shearer) and stars whose national identity is integral to their perception as they age (Riva, Bachchan, Pavor). There are stars from the beginning of Hollywood (Valentino, Reid) to the present day (Jolie), and those who made uneasy transitions between countries (Mason), ages (Ringwald) and industrial eras (Keaton). The book examines the range of factors that affect how star images endure, including appropriate and inappropriate ageing (Griffith), race (Ice Cube) and digital technologies (Lee). .
Keywords: Culture -- Study and teaching; Communication; Motion pictures -- History; Motion pictures; Motion picture acting; Performing arts; Cultural and Media Studies; Media Studies; Film History; Film Theory; Screen Performance; Performing Arts; Electronic books